Assessment of the impact of good pharmacy practices training among drug dispensers in Bangladesh - Ali, Sunjida Binta; Chakma, Nantu; Islam, Md. Saimul; Amzad, Raian; Khan, Md. lftakhar Hassan; Aziulla, Md.; Momtaz, Tanisha; Azad, Abul Kalam; Babar, Zaheer-Ud-Din; Naheed, Aliya (Frontiers in Pharmacology, 2023)
Background:Training improves dispensing behavior of drug dispensers in the low- and middle-income countries.Between 2018 and 2020, a total of 5,059 Grade C pharmacists, who complete a 3-month training course for availing a“Grade C pharmacist certificate” were trained on Good Pharmacy Practice (GPP) in 11 districts in Bangladesh by Management Sciences for Health (MSH) under Better Health in Bangladesh (BHB) project.We assessed the impact of GPP among trained Grade C pharmacists under the BHB project compared to those who did not receive GPP training under the BHB project (non-trained), and explored the major challenges towards achieving GPP. Methods:We created a database of trained Grade C pharmacists provided by MSH and randomly selected the trained Grade C pharmacists for recruitment following consent.We created another database of the non-trained Grade C pharmacist who were deployed within one-kilometer radius of a trained Grade C pharmacists, and randomly recruited one non-trained against one trained Grade C pharmacists.A semi structured questionnaire was administered to obtain information about knowledge ofGPP, including guidelines of dispensing medicines, temperature maintenance, medicine storage, counseling customers and labeling medicines. Dispensing behavior was directly observed following a structured tool.Chi-square test (for categorical variables) and independent sample t-tests (for continuous variables) were applied for comparison between the trained and non-trained Grade C pharmacists.A logistic regression model was applied to explore an association between knowledge and practice between the two groups. Results:Between FebruaryandMarch2021,220 trained and220 non-trained GradeC pharmacists were recruited. Mean age(SD) of the participants was 41years(10.5) and98.4% was male. Compared to the non-trained, the trained Grade C pharmacists had better knowledge about the guidelines of dispensing medicines (97.7% vs.89.5%,P<0.001),temperaturecontrol (91.8%vs.45.5%,P=0.001),medicine storage (92.3% vs.40.5%,P=0.001)counseling customers (99.5%vs.92.3%,p<.001) and labelingmedicines(91.0%vs.80%,P<0.001).General dispensing behavior was observed tobe better among the trained than the non-trained with labeling of medicines (63.2% vs.53.4%,P=0.038), counseling customers (39.1% vs.28.6%,P=0.021) and using room thermometer for maintaining ambient temperature in medicine shop(56.8% vs.26.8%, P<0.001).Bad behavior of the customers(39.5%) and lack ofGPP knowledge amongGrade C pharmacists (28.6%) were recognized to be challenges towards achieving GPP in Bangladesh. Conclusion:Training led to betterknowledge and practices about dispensingmedicines among Grade C pharmacists in Bangladesh.Periodictraining may promote achieving GPP in Bangladesh.